Nutritional assessment of pregnant and lactating women in an urban slum of Siddipet District, Telangana, India - Hothur, Rekha; Patruni, Manoj (International Journal Of Community Medicine And Public Health, 2020)
Background: One of the vulnerable groups among the population is pregnant and lactating mothers. Among the women in pregnancy it effects the fetal growth and development. Aim of this study is to assess the dietary pattern of pregnant women and lactating mothers and factors related with adequacy of nutrient intake. Methods: Community based cross-sectional study. Study setting was urban slum dwellers of Siddipet. Study period from September 2019 to November 2019. Study population were pregnant and lactating women up to 6 months registered in Anganwadi centre. Sample size was 91 pregnant and 58 lactating women. Sampling methods was simple random sampling method. Data analysis used was SPSS Version 21. Results: Distribution of women according to intake of nutrients revealed that nearly 90% of the pregnant and 50% of the lactating women were not taking adequate calories and proteins respectively. Mean calorie intake in pregnant and lactating women was 1418±192 and 1600±218 respectively (recommended dietary allowance (RDA) for calories in pregnant and lactating women was 2580 kcal and 2830 kcal respectively). Mean protein intake in pregnant and lactating women was 47±9 and 51±8 respectively (RDA for protein in pregnant and lactating women was 78 gm and 74 gm respectively). Food taboos were prevalent in both pregnant (42%) and lactating women (55%). Conclusions: Interventions for promoting health education in women need to be strengthened, in order to achieve proper nutrition to women and mothers.